An exploratory study of King IV™: The effect of Principle Four and its practices in achieving good performance by selected JSE-listed companies - Rohlandt, John (Rhodes University, Faculty of Commerce, Rhodes Business School)
The research conducted for the dissertation entitled "An exploratory study of King IVTM: The effect of principle four and its practices in achieving good performance by selected JSE-listed companies" , aimed to determine whether principle four, namely the creation of value, and the application by an organisation of the recommended practices as set out in King IVTM, contribute to the achievement of good performance. The research outlined the background to the research by describing the history of the development of corporate governance internationally and in South Africa, dating back to 1932 and culminating with the King IV™ report. It described the problem statement, defined the aims and objectives of the study, and demonstrated that the significance of the study lies in its exploration of the relationship between the King IV™ practices and good performance. The research also provided a review of the related literature, describing the theoretical background for the research, which includes the conceptual framework and propositions of the research. The research was situated in the post-positivist paradigm, the methodology was qualitative, and the method adopted was a theory-based evaluation, based on a deductive thematic analysis with pattern matching. From a detailed reading of the integrated reports and the King IVTM compliance registers of the fifteen selected listed companies for the years 2017 to 2019, hits and misses in relation to the six capitals and the eight associated practices were recorded. From this, the resulting descriptive statistics were calculated and set out in the form of tables, and a regression analysis was used to support the findings. The research revealed, based on the descriptive statistics data that there is a moderate relationship between good performance and the application of the eight practices set out in King IVTM, that contribute to the achievement of good performance. It was, therefore, concluded that the adoption of corporate governance principles and practices has an effect on performance, although it may not be significant. It is also concluded that the application of the practices in terms of principle four as set out in King IVTM is achieving its intended outcome - the creation of value. The research also concluded that good performance constitutes more than just a company performing financially and that all companies need to comply with the requirements of King IVTM, as the Code is designed to guide organisations in achieving good corporate governance. Governance principles and practices should be adopted in a way that does not unduly constrain them and is appropriate to a company's particular circumstances. Complying with corporate governance principles and implementing the recommended practices might not guarantee positive outcomes (good performance), but it will guide the board of directors in the pursuit of ethical and effective leadership, and that of sustainable development in order to meet the needs of all stakeholders.
Keywords: Corporate governance -- South Africa; Organizational performance; value creation; Business planning; Social responsibility of business -- South Africa